Biopriming Techniques for Improving Germination and Seedling Growth in Indian Sandalwood (Santalum album L.) - Debta, Harish; Kunhamu, T. K.; Santhoshkumar, A. V.; Jamaludheen, V.; Binu, N. K.; Jisha, K. C. (International Journal of Economic Plants, 2024)
The present study was conducted during April, 2022 to September, 2023 with an aim to screen out the most effective biopriming treatment for improving the regeneration related constraints and seedling growth of Indian sandalwood (Santalum album L.), an IUCN- Vulnerable category tree species, that are under severe threat due to illegal harvesting and over exploitation in the wild. We tried five biopriming agents (e.g. Effective microorganisms; Plant growth promoting rhizobacteria (PGPR-I and PGPR-II); Pseudomonas fluorescens and Piriformospora indica) with four uniform durations of treatments i.e. 2, 4, 6 and 8 days. The results revealed that biopriming with Pseudomonas fluorescens for eight days recorded the highest germination percentage (70.67%) and the highest germination rate index (0.84). Pseudomonas fluorescens mediated biopriming followed by longer durations of PGPR-I and Piriformospora indica treatment (6-8 days) effectively lowered the imbibition period, mean germination time and increased germination rate. The seedling vigour index improved substantially due to the application of Pseudomonas fluorescens and PGPR-I. Hence, we recommend biopriming with Pseudomonas fluorescens, longer duration of PGPR-I and Piriformospora indica as a potential technique for overcoming the germination constraints in sandalwood and producing seedlings with high vigour.